Depletion of RNA-binding protein RBM8A (Y14) causes cell cycle deficiency and apoptosis in human cells. (August 2013) - Ishigaki, Yasuhito; Nakamura, Yuka; Tatsuno, Takanori; Hashimoto, Mitsumasa; Shimasaki, Takeo; Iwabuchi, Kuniyoshi; Tomosugi, Naohisa
RBM8A (Y14) contains an RNA-binding motif and forms a tight heterodimer with Magoh. The heterodimer is known to be a member of the exon junction complex that forms on mRNA before export and it is required for mRNA metabolism processes such as splicing, mRNA export and nonsense-mediated mRNA decay. Recently, deficient cellular proliferation has been observed in RBM8A- or Magoh-depleted cells. These results prompted us to study the role of RBM8A in cell cycle progression of human tumour cells. The depletion of RBM8A in A549 cells resulted in poor cell survival and the accumulation of mitotic cells. After release from G1/S arrest induced by a double thymidine block, the RBM8A-silenced cells could not proceed to the next G1 phase beyond G2/M phase. Finally, the sub-G1 population increased and the apoptosis markers caspases 3/7 were activated. Silenced cells exhibited an increased frequency of multipolar or monopolar centrosomes, which may have caused the observed deficiency in cell cycle progression. Finally, silencing of either RBM8A or Magoh resulted in mutual downregulation of the other protein. These results illustrate that the RBM8A-Magoh mRNA binding complex is required for M phase progression and both proteins may be novel targets for anticancer therapy.